Integration of Performance Tasks in Grade 12 Physical Education: Basis for Policy Enhancement - Reyes, Mark Anthony O. (Randwick International of Education and Linguistics Science Journal, 2024)
This action research investigates the impact of integrating performance tasks in the Physical Education curriculum for Grade 12 students at Libertad National High School. The study's objective was to determine this approach's effectiveness as a foundation for potential policy enhancements. Using a pre-test and post-test design, students' grades before and after the intervention were analyzed through a t-test to identify significant differences. The results showed a statistically significant improvement in students' grades, highlighting the positive impact of performance-task integration on academic achievement in Physical Education. These findings support the inclusion of task-based assessments within the PE curriculum, indicating that such strategies can enhance student engagement, alleviate stress, and foster critical thinking skills. It is recommended that schools implement performance tasks more broadly in PE and explore the potential for integrating these strategies into other core subjects. By providing targeted teacher training and allocating sufficient resources, schools can effectively incorporate performance tasks across various subjects, enriching the overall educational experience and supporting deeper student learning.